PS-B05-11: IMPAIRED CELL INTERACTIONS AT THE PRE-ECLAMPTIC MATERNAL-FOETAL INTERFACE. (January 2023) - Nonn, Olivia; Debnath, Olivia; Valdes, Daniela; Sallinger, Katja; Secener, Ali Kerim; Haider, Sandra; Tiesmeyer, Sebastian; Coscia, Fabian; Heliebi, Amin El; Tilaganathan, Basky; Mueller, Dominik N; Huppertz, Berthold; et al.
Abstract : Hypertensive disorders in pregnancy, of which the multisystem syndrome pre-eclampsia is most severe, leading to preterm delivery, maternal mortality and life-long complications1. Pre-eclampsia lacks early screening tools2, 3 and causal therapies4, 5. To elucidate early disease dynamics, we present the first spatio-temporal study comparing single-nuclei transcriptomes of human preterm pre-eclamptic placentae and healthy controls, contextualising this in a comprehensive study including early and late gestational placentae and implementing spatial multi-omics methods. Here we show trophoblast pre-fusion cells and their developmental trajectory running towards a novel trophoblast cell-state we identify as juvenile syncytiotrophoblast. We found that disturbed trophoblast development, reconstructed by spatial multi-omics and including early dysregulation in differentiation-driving transcription factor p300, likely initiates pre-eclampsia. We suggest pre-eclampsia to be a disease of dysregulated syncytiotrophoblast differentiation: Disease-specific premature differentiation of the maternal-foetal barrier leads to a senescent syncytiotrophoblastic interaction through maternal circulation with maternal vessels. This initiates a disrupted decidual maternal response via LEP, GDF15 and INHBA. Our results highlight a disturbed cellular communication from foetal to maternal side during the development of pre-eclampsia starting with a disturbed trophoblast maturation. We provide new targets for potential early disease prevention in order to protect mother and child from increased gestational mortality and morbidity but also from life-long increased cardiovascular disease risk.